2017
DOI: 10.1089/jamp.2016.1343
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Drug Delivery During Noninvasive Positive Pressure Ventilation: Effects of Intersubject Variability and Excipient Enhanced Growth

Abstract: The EEG approach enabled high-efficiency lung delivery of aerosols administered during NPPV and reduced intersubject aerosol delivery variability by an order of magnitude. Use of an in-line DPI device that connects to the NPPV mask appears to be a convenient method to rapidly administer an EEG aerosol and synchronize the delivery with inspiration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…Airflow is not included through the mouth opening, consistent with a subject breathing nasally. Based on the study of Walenga et al (11), deposition in this nasal model was similar to deposition in other models over a range of surface area to volume ratios for particle diameters of approximately 1.5 μm. The model was built using Accura ClearVue by 3D Systems On Demand Manufacturing.…”
Section: Airway Modelssupporting
confidence: 75%
See 2 more Smart Citations
“…Airflow is not included through the mouth opening, consistent with a subject breathing nasally. Based on the study of Walenga et al (11), deposition in this nasal model was similar to deposition in other models over a range of surface area to volume ratios for particle diameters of approximately 1.5 μm. The model was built using Accura ClearVue by 3D Systems On Demand Manufacturing.…”
Section: Airway Modelssupporting
confidence: 75%
“…In transitioning to other formulations, maintaining a highly dispersible powder will be a key requirement. In previous work, we have demonstrated that highly dispersible EEG formulations can be made with terbutaline sulfate (38) and ciprofloxacin (8,11,39). The development of spray dried EEG surfactant formulations is also in progress (40,41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, considering aerosol delivery simultaneously with LFNC therapy, the steady flow cannula emitted dose was 75% of the capsule loaded dose and, with cyclic inhalation, up to 55% of the loaded dose reached a tracheal filter. In a similar study with a positive pressure DPI, Walenga et al (53) previously demonstrated high efficiency lung delivery of an EEG aerosol through a mask interface during noninvasive positive pressure ventilation.…”
Section: Discussionmentioning
confidence: 85%
“…I nline dry powder inhalers (DPIs) are actuated by a stream of gas that is passed through the device from an external positive pressure source. (1)(2)(3)(4) These devices are useful for generating and delivering an aerosol to patients that may not be able to use a DPI such as children younger than approximately 5 or 6 years. (5)(6)(7) The positive pressure gas source can be used to assist with deep inspiration and help maintain a breath hold in individuals with compromised lung function.…”
Section: Introductionmentioning
confidence: 99%